Contribuição ao controle de um sistema de geração a velocidade variável utilizando gerador de indução duplamente excitado. - Rodrigo Gaiba de Oliveira (2009)
The variable speed wind power plants, equipped with doubly-fed induction generator, are configured as the most used generation system in worldwide, mainly, due the active and reactive power control ability and, also, due the reduced power converter, which is dimensioned only for a fraction of the generator rated power. Moreover, the main drawback of this system is its sensitivity to the grid disturbances during voltage sags, mainly, due to the direct grid connection of the stator windings. Based on this context and in the recent grid codes, this work has as main goal the study and development of control strategies that allows the wind turbine to stay connected during grid disturbances and, additionally, the improvement of the ability to support the grid, through reactive power injection. With this approach that is preceded of the development of an experimental test bench and experimental results that ripen the knowledge about important aspects of this technology, this work developed a dynamic behavior study of the doubly-fed induction generator, identifying the main problems associated to the wind generation system control. A control strategy that provide greater damping to the stator flux oscillations, during transients, was developed increasing the ride-through fault capability of these wind generators. A reactive power shared control strategy is proposed and experimentally implemented using both power converters to give reactive power support to the grid.